Sistem Pusat Informasi Spasi Berbasis Android Studi Kasus Program Studi Sistem Informasi Universitas Malikussaleh - Ananda Faridhatul Ulva; Angga Pratama; Yunia Silfitri (Jurnal Tika, 2021)
Information is data that is presented in a more useful form that is used to make decisions. In the Information Systems Study Program, information is very important to improve the performance of the Study Program, but the problem that often occurs is the lack of services to obtain and convey information, this makes it difficult for students and lecturers to find out the latest information and information about academics. Therefore, we need an application that can be used by students and lecturers to obtain and convey information. The information displayed is in the form of student and lecturer profile information, information about final project students, practical work students, real work college students, lecture schedule information and teaching schedules as well as information that can be added by lecturers in the application which can later be seen by all users. This android-based mobile programming application was built using the programming language dart. The design tool used is a unified modeling language (UML) with the system development method using the method waterfall. With this application, the Study Program has more effective information media and can assist students and lecturers in obtaining and conveying information easily anytime and anywhere